Liver iron concentrations and urinary hepcidin in β-thalassemia - ORIGA, Raffaella; GALANELLO, Renzo; GANZ, Tomas; GIAGU, Nicolina; MACCIONI, Liliana; FAA, Gavino; NEMETH, Elizabeta (Haematologica (Roma), 2007)
Patients with beta-thalassemia, like those with genetic hemochromatosis, develop iron overload due to increased iron absorption, and their iron burden is further exacerbated by transfusion therapy. Hepcidin, a hepatic hormone, regulates systemic iron homeostasis by inhibiting the absorption of iron from the diet and the recycling of iron by macrophages. In turn, hepcidin release is increased by iron loading and inhibited by erythropoietic activity. Hepcidin deficiency is the cause of iron overload in most forms of hereditary hemochromatosis. We sought to determine hepcidin's role in the pathogenesis of iron overload in b-thalassemia. We assessed the degree of iron overload in thalassemia intermedia and major patients by measuring hepatic iron concentration in liver biopsy samples and serum ferritin, estimated erythropoietic drive by assaying soluble transferrin receptor and serum erythropoietin levels and correlated these with urinary hepcidin measurements. Urinary hepcidin levels in beta-thalassemia demonstrate severe hepcidin deficiency in thalassemia intermedia. There was a strong inverse relationship between urinary hepcidin levels and both erythropoietin and soluble transferrin receptor, markers of erythropoietic activity. In contrast, hepcidin levels were elevated in thalassemia major, presumably due to transfusions that reduce erythropoietic drive and deliver a large iron load. Despite similar liver iron concentrations in the two conditions, serum ferritin was much lower in thalassemia intermedia. In thalassemia intermedia, high erythropoietic drive causes severe hepcidin deficiency. The lack of hepcidin results in hyperabsorption of dietary iron, but also in iron depletion of macrophages, lowering their secretion of ferritin and, consequently, serum ferritin levels. In contrast, in thalassemia major, transfusions decrease erythropoietic drive and increase the iron load, resulting in relatively higher hepcidin levels. In the presence of higher hepcidin levels, dietary iron absorption is moderated and macrophages retain iron, contributing to higher serum ferritin. In the future, hepcidin measurements may allow a more accurate assessment of the degree of iron overload and the maldistribution of iron in thalassemia.